The specialization continuum in pollination systems: diversity of concepts and implications for ecology, evolution and conservation - Armbruster, William Scott (Functional ecology, 2017)
Summary Specialization in plant–pollinator relationships is a core concept in discussions of plant evolution and ecology; it is central to our thinking, not just about the ecology of plant–pollinator interactions and pollinator services, but also about reproductive isolation, speciation, extinction and assembly of communities. However, as reviewed here, the concept ‘plant–pollinator specialization’ has multiple definitions and uses, and these disparate uses have engendered confusion in the literature. Organizing these disparate uses into a comprehensive framework is an overdue task, prior efforts notwithstanding. This contribution attempts to make clear the variation in meaning and usage of plant–pollinator specialization, including distinguishing between ecological specialization (interacting with few partners or resources), evolutionary specialization (genetic change associated with increased specialization) and phenotypic specialization (having specialized or derived phenotypic traits), with application of all three concepts to both plants and flower‐visiting animals. These variations in interpretation of specialization affect how we view evolutionary and biogeographical trends, as well as extinction risk. In the light of this conceptual diversity, I evaluate the relationships between specialization and possible trends in floral evolution and rates of speciation and extinction. I also address several implications of specialization for community ecology and resilience of pollination services in the face of environmental disturbance. A lay summary is available for this article. Lay Summary